2005
DOI: 10.1007/s00380-004-0795-3
|View full text |Cite
|
Sign up to set email alerts
|

Early protective effects of iloprost, a stable prostacyclin analog, during spinal cord ischemia in a rabbit model

Abstract: Spinal cord ischemia may develop into paraplegia in some cases during operation of the thoracoabdominal aorta. This is attributable to the vulnerability of spinal motor neurons to ischemia. In this study, iloprost was used as an agent to decrease the severity of ischemia and reperfusion injury to the spinal cord motor neurons. Twenty-one rabbits were randomized into three groups of seven animals each: group A (iloprost not administered), group B (25 ng/kg per minute iloprost), and group S (sham-operated). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…It was reported in several studies [2,23,24] that iloprost infusion started before aortic occlusion and continued throughout ischemia may result in significant spinal cord protection.…”
Section: Discussionmentioning
confidence: 97%
“…It was reported in several studies [2,23,24] that iloprost infusion started before aortic occlusion and continued throughout ischemia may result in significant spinal cord protection.…”
Section: Discussionmentioning
confidence: 97%
“…It was reported that the protective effects against increasing of lipid peroxidation caused by I/R were shown in rats treated with different dosages (range, 30 -100 mg/kg) of vitamin C [33]. Different dosages of iloprost (range, 20 -300 ng/ kg/min) have the protective effects on reperfusion damage [34,35]. In addition to Tadros et al [36] 20 ng/kg/ min of iloprost as in the hepatic I/R study performed by to obtain the maximal physiological effect.…”
Section: Discussionmentioning
confidence: 99%
“…7 Similarly, iloprost infusion started before aortic occlusion and continued throughout the ischemia may also result in significant spinal cord protection which is consistent with the findings of several studies. 8,26,27 The addition of iloprost to NAC improved neurological outcome, compared with NAC given alone, suggesting that a synergistic effect exits for these drugs when given in combination (p!0.01). The cytoprotective effect of NAC is attributed to its regulatory role on microcirculatory blood flow and tissue oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] Pharmacologic research such as use of steroids, oxygen-derived free radical scavengers, vasodilators, and drugs designed to achieve spinal cord electrical silence during ischemia-reperfusion is of continuing interest. [7][8][9][10] Neuronal cell death during ischemia is thought to be due to free radical generation, lipid peroxidation, and the accumulation of intracellular calcium. 11,12 Glutathione is present in high concentration in most of the cells which have antioxidant properties.…”
Section: Introductionmentioning
confidence: 99%